Prevalence of Depression among Patients admitted to Baquba Teaching Hospital - Hammod, Hyder J; Ahmed, Basim M (Diyala Journal of Medicine, 2018)
Background: Depression is common in patient both surgical and medical cases and has independently variable prognosis according many factors related to patient and variable disorders. Objective: To study prevalence of depression in in-patient s admitted to Baquba Teaching hospital and evaluates the clinical value of depression and severity of depression among them. Patients and Methods: Seven hundred and seven patients admitted to Baquba Teaching hospital in different branches of medicine, this descriptive study was conducted throughout the period between 1st September 2015 to 12th August 2016, were evaluated for demographic distribution and depression by using diagnostic and statistical manual of mental disorders 4th edition scale that depend on main symptoms of depression (version 10), the results were evaluated statistically, mean of score, frequency and percentage were used as statistical methods to analyze the data obtained. Results: Sixty eight (8.8%) out of 707 with depression, more common in female 42 (62%) than that in male 26 (38%) also in housewives than employed and in younger age groups than older and in more in early days of admission than later days. Conclusion: Depression in In-patient usually common, and need consultation of psychiatrists, to help them .Depression play important role in prognoses .of disorders and compliance of patient to therapy. We suggest that every hospital need psychiatrist to diagnose and treat depression comorbid with diseases.